2017
DOI: 10.1146/annurev-anthro-102116-041702
|View full text |Cite
|
Sign up to set email alerts
|

Personal Narratives and Self-Transformation in Postindustrial Societies

Abstract: This article surveys literature on personal narratives as situated practices in a variety of contexts in primarily Western, postindustrial societies. It begins with an overview of theories that articulate the relationships among narrative, self, and narrating context. I then consider how narratives of the self are shaped in institutional contexts, including those in which narratives are used to evaluate selves or used as a technology for changing selves. The section that follows examines how narrative analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 108 publications
(131 reference statements)
0
14
0
1
Order By: Relevance
“…When evaluation researchers explicitly ask participants how a BIP changed them, they say it helped them take responsibility, develop empathy, and learn self‐control (Scott and Wolfe ; Silvergleid and Mankowski ). Although some view this as evidence of effectiveness, we see it as evidence that participants can produce a “self‐transformation story” (Dunn ) if asked to do so.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…When evaluation researchers explicitly ask participants how a BIP changed them, they say it helped them take responsibility, develop empathy, and learn self‐control (Scott and Wolfe ; Silvergleid and Mankowski ). Although some view this as evidence of effectiveness, we see it as evidence that participants can produce a “self‐transformation story” (Dunn ) if asked to do so.…”
mentioning
confidence: 79%
“…However, some people reject and/or subvert an organization's “preferred narratives [because they] become constraining and even coercive” (Dunn :70). Loseke (:123) finds that women seeking refuge in battered women's shelters or support groups sometimes reject the formulaic “Wife Abuse Story”—which portrays them as pure victims and men as pure villains—because it leaves out the “relational core” of their experiences and is “disempowering.” Kaiser () shows that women whose cancer is in remission reject treatment centers' “survivor” identity because they fear they will not survive.…”
Section: Self‐narratives In Social Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, sociolinguistically oriented research found that children were socialized into the language of anxiety through the grammar and discourse structure of their mother’s narratives (Capps and Ochs 1995). Narratives have also been used as emotional pedagogy in public speaking classes to promote positive thinking and personal transformation (Dunn 2014, 2016), and narrative templates in communities may also contribute to individual members’ reinterpretation of their past and reshaping of self at present (Dunn 2017). Institutions promote narrative templates that frame individuals as innovative, risk‐taking, personally agentive, and responsible.…”
Section: The Role Of Narrative‐in‐interaction In Language Socializationmentioning
confidence: 99%
“…At the same time, linguistic anthropologists have been cautious about emphasizing the affordances of digital media as having a deterministic effect on communicative practices. Gershon (, 16) reminds us that “the newness of new media lies not in the technology, but in the sociomaterial practices that linguistic anthropologists’ analytical concepts render visible,” emphasizing the need to attend to the intersection of ideologies about new media and language users’ practices as they make sense of the technological resources available for communication (see also Dunn ; Reyes ). Indeed, relatively “old” technology, such as television, may serve as a medium for “new” communicative practices, such as when live television broadcasts of events back in the homeland give rise to a new sense of diasporic imagination (Saleh ) or when nongovernmental organizations in East Africa adopt participatory formats for the television shows they produce to position the participants and viewers as active, liberal‐minded citizens (Ivanova ).…”
Section: Digital Practices and The Politics Of Online Communicationmentioning
confidence: 99%